A Review on The Role of VEGF in Tamoxifen Resistance - Mansouri, Sepideh; Feizi, Nikta; Mahdi, Ali; Majidzadeh-A, Keivan; Farahmand, Leila (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background: Certain molecular deviations can lead to the development of breast cancer. For instance, estrogen and estrogen receptors play a significant role in inducing tumor proliferation. However, the efficacy of endocrine therapy through the administration of anti-estrogen drugs, such as Tamoxifen, is challenged by acquired resistance. Methods: Relevant articles were retrieved from Medline and google scholar. All were screened to select the ones discussing the molecular mechanisms of angiogenesis and Tamoxifen resistance. The molecular interactions contributing in the resistant network were studied from the eligible articles. Results: Tamoxifen resistance occurs as a consequence of over-activated signal transduction pathways such as RTK s dependent cascades. It has been shown that microvessel count was greater in Tamoxifen resistant tissues than in responsive ones. Conclusion: In this review, the interaction between estrogen, Tamoxifen, VEGF, and VEGF receptors (VEGFRs) in Tamoxifen resistant cells has been discussed. VEGF and estrogen-independent growth cascades, especially MAPK have a positive feedback loop in Tamoxifen resistant cells. It has been proposed that over-activated pathways in Tamoxifen resistant cells induce pin1 mediated VEGF over-expression, which in turn result in enhanced activation of MAPK.
Keywords: breast cancer